Developing Culturally Responsive Transition Plans Using the Indicator 13 Checklist - Walker, Allison R.; Brophy-Dick, Alicia (Journal of the American Academy of Special Education Professionals, 2019)
Research has shown that there are consistently poor post-school outcomes for students with disabilities, especially for students from culturally and linguistically diverse (CLD) backgrounds. Therefore, it is important for educators to develop culturally responsive transition plans for youth from CLD backgrounds that address their needs. Professionals working with this population can also benefit from using the National Secondary Transition Technical Assistance Center’s (NSTTAC) Indicator 13 checklist when developing these transition plans. Using a vignette, this article outlines a step-by-step process for familiarizing oneself with the Indicator 13 checklist, identifying one’s own cultural values and the family’s values, and identifying the difference between the educator’s and family’s values as a suggested practice for developing a cohesive and culturally responsive transition plan.